THE INFLUENCE OF ORGANIZATIONAL CULTURE, TRANSFORMATIONAL LEADERSHIP AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Yasman; Ratnawati; M. Taufiq Noor Rokhman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aimed to determine the relationship between work motivation, transformational leadership, organizational culture, and employee performance at PT Indolakto Pasuruan. The data of this study used quantitative methods obtained through questionnaires distributed to 84 respondents, consisting of production employees, and the analysis was carried out using the SEM-PLS method. This study concluded that organizational culture and transformational leadership style directly and significantly influence work motivation and employee performance. Mediation analysis showed that work motivation mediates the relationship between organizational culture and transformational leadership style with employee performance. This finding supports the managerial strategy of PT Indolakto Pasuruan to improve employee performance, requiring the implementation of a work culture through core values by enforcing work discipline for its employees and transformational leadership that provides an ideal influence for its employees by being a role model, having high integrity, and submitting to and complying with all rules.